Comparative analysis of uniplanar external fixator and retrograde intramedullary nailing for ankle arthrodesis in diabetic Charcot's neuroarthropathy - Shah, Nakul S (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Charcot's neuroarthropathy of ankle leads to instability, destruction of the joint with significant morbidity that may require an amputation. Aim of surgical treatment is to achieve painless stable plantigrade foot through arthrodesis. Achieving surgical arthrodesis in Charcot's neuroarthropathy has a high failure rate. This is a retrospective nonrandomized comparative study assessing the outcomes of tibio-talar arthrodesis for Charcot's neuroarthropathy treated by uniplanar external fixation assisted by external immobilization or retrograde intramedullary interlocked nailing. MATERIALS AND METHODS: Records of the authors′ institution were reviewed to identify those patients who had undergone ankle fusion for diabetic neuroarthropathy from January 1998 to December 2008. A total of11 patients (six males and five females) with a mean age of 56 year and diabetes of a mean duration of 15.4 years with ankle tibio-talar arthrodesis using retrograde nailing or external fixator for Charcot's neuroarthropathy were enrolled for the analysis. Neuropathy was clinically diagnosed, documented and substantiated using the monofilament test. All procedures were performed in Eichenholz stage II/III.Six patients were treated with uniplanar external fixator, while the remaining five underwent retrograde intramedullary interlocking nail. The outcomes were measured for union radiologically, development of complications and clinical follow-up, according to digital archiving systems and old case notes. RESULTS: All five (100%) patients treated by intramedullary nailing achieved radiological union on an average follow-up of 16 weeks. The external fixation group had significantly higher rate of complications with one amputation, four non unions (66.7%) and a delayed union which went on to full osseous union. CONCLUSION: The retrograde intramedullary nailing for tibio-talar arthrodesis in Charcot's neuroarthropathy yielded significantly better outcomes as compared to the use of uniplanar external fixator.